Effect of tide on flood modelling and mapping in Kota Tinggi - Ismail, Ahmad Zuhdi (2015)
This study aimed at mapping the Kota Tinggi flood in 2006/07 that had caused massive damages to properties and the environment. The flood was associated with unusually high intensity and continuous rainfall. Therefore, a reliable technique of floodplain mapping is crucial for the improvement of flood control strategies and preparing an evacuation plan. The main objective of this study is to compare the effect of tide on flood modelling analysis. The inundated areas were mapped for various annual recurrent intervals (ARIs) using peak flow data from July 1965 to Jun 2010. The study used Light Detection and Ranging (LiDAR) data for flood modelling. HEC-HMS, HEC-RAS, and HEC-GeoRAS were used to develop the flood modelling. The results reaffirm that the GEV model is the best for fitting the annual flood. The HEC-HMS hydrologic model was calibrated and validated using observed hydrographs in September 2002 and January 2003, respectively. Upon successful calibration and validation, the model was used to simulate flood hydrograph in January 2007. The modelling took into account tidal effect. When tidal effect was not considered, the simulated flood depth was 43 % lower than the observed flood. However, the inclusion of tidal effect has reduced the simulation error with average similarity of 91.4%. The simulation results show that the river flow starts to over bank for ARIs exceeded 25 year.